Incidence and predictors of hepatocellular carcinoma in autoimmune hepatitis: A multicenter international study. (March 2023) - Colapietro, F.; Maisonneuve, P.; Lytvyak, E.; Beuers, U.; Verdonk, R.; van der Meer, A.; van Hoek, B.; Kuiken, S.J.; Brouwer, H.; van der Wouden, E.J.; Muratori, P.; Aghemo, A.; et al.
Abstract : Background and Aim: Survival in patients with Autoimmune Hepatitis (AIH) is impaired mostly due to potential evolution to liver cirrhosis. While cirrhosis is a well-known precursor of Hepatocellular Carcinoma (HCC), the risk of HCC in AIH remains unclear. Aim of our research was to investigate the risk of HCC across a global AIH cohort and to identify predictive factors. Methods: We performed a retrospective, observational, and multicentric study of data collected within the International Autoimmune Hepatitis Group (IAIHG) Retrospective Registry. All adult and pediatric patients with regular and complete follow-up concerning demographic, clinical, biochemical and treatment data were included. Outcome considered was HCC development. Results: 1421 patients from 22 centers across Europe and Canada were included, with a median follow-up of 11.6 years. 285 (20.9%) patients were already cirrhotic at diagnosis, PBC and PSC variant syndromes were observed in 119 (8.4%) and 95 (6.7%) patients. During follow up, 24 patients developed HCC (1.7 %) with cumulative incidence of HCC of 0.6% (95% CI 0.3-1.2) at 5 years, 0.7% (95% CI 0.4-1.3) at 10 years, 2.6% (1.4-4.3) at 20 years, and 6.4% (3.0-11.6) at 30 years of follow-up. Patients developing cirrhosis during follow-up had a significantly higher incidence of HCC with a cumulative risk increasing over time from 3.1% at 5 years to 12% at 30 years from AIH diagnosis. Older age (HR 3.96, p = 0.01), obesity (HR 3.62, p = 0.04), cirrhosis (HR 3.44, p = 0.02), and PSC variant (HR 8.80, p < 0.001) at baseline resulted independent risk factors for HCC development at multivariate analysis stratified by center. Conclusion: The incidence of HCC in AIH is low even after cirrhosis development; age more than 40 years, obesity, cirrhosis, and PSC variant syndrome at baseline represent independent risk factors for HCC development. Further studies are needed to identify predictive tools for enhanced stratification of the at-risk population to design "a la carte" surveillance strategies.